Respuesta :

[tex] (f+g)(x)=4x^2+1+x^2-5=5x^2-4 [/tex]

MarkV
Hi there!

[tex](f +g )(x) = f(x) +g (x)[/tex]
In other words: to find (f + g)(x) we must add up the functions f(x) and g(x). Substitute both functions into the formula.

[tex](f + g)(x) =( 4x {}^{2} + 1) + ( {x}^{2} - 5)[/tex]
Remove the parenthesis, since they don't have a function in this situation.

[tex](f + g)(x) =4x {}^{2} + 1 + {x}^{2} - 5[/tex]
Rearrange the expression in order to collect terms later.

[tex](f + g)(x) = 4x {}^{2} + {x}^{2} + 1 - 5[/tex]
And finally collect the terms.

[tex](f + g)(x) = 5x {}^{2} - 4[/tex]
~ Hope this helps you!